Nuclear Co-translocation of Myotrophin and p65 Stimulates Myocyte Growth: REGULATION BY MYOTROPHIN HAIRPIN LOOPS - Das, Biswajit (American Society for Biochemistry and Molecular Biology, 2008)
Myotrophin, a 12-kDa ankyrin repeat protein, stimulates protein synthesis and cardiomyocyte growth to initiate cardiac hypertrophy by activating the NF-κB signaling cascade. We found that, after internalization into myocytes, myotrophin cotranslocates into the nucleus with p65 to stimulate myocyte growth. We used structure-based mutations on the hairpin loops of myotrophin to determine the effect of the loops on myotrophin and p65 localization, induction of protein synthesis, and cardiac hypertrophy. Loop mutants, most prominently glutamic acid 33→alanine (E33A), stimulated protein synthesis much less than wild type. Myotrophin-E33A internalized into myocytes but did not translocate into the nucleus and failed to promote nuclear translocation of p65. In addition, two cardiac hypertrophy marker genes, atrial natriuretic factor and β-myosin heavy chain, were not up-regulated in E33A-treated cells. Myotrophin-induced myocyte growth and initiation of hypertrophy thus require nuclear co-translocation of myotrophin and p65, in a manner that depends crucially on the myotrophin hairpin loops.